Pelatihan Pelajar Hebat Untuk Menurunkan Perilaku Tidak Disiplin Siswa SMP Negeri 1 Yogyakarta - Ayatullah Kutub Hardew (Academic Journal of Psychology and Counseling, 2022)
Some students often display unruly behaviors during in classroom environment. This situation may hinder the class from achieving national education objectives. This study aimed to examine the effectiveness of Excellent Student Training in lowering the prevalence of undisciplined behaviors among students. This study was conducted at SMP Negeri 1 Yogyakarta. It used an experimental approach with the single case A-B-A withdrawal design. Researchers implemented the visual conservative dual-criterion (CDC) method for the data analysis. Based on the unruly behavior graph, it was found that the Excellent Student Training is effective for reducing unruly behavior incidence.